If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + 3(n + -1) = 9 Reorder the terms: N + 3(-1 + n) = 9 N + (-1 * 3 + n * 3) = 9 N + (-3 + 3n) = 9 Reorder the terms: -3 + N + 3n = 9 Solving -3 + N + 3n = 9 Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '3' to each side of the equation. -3 + N + 3 + 3n = 9 + 3 Reorder the terms: -3 + 3 + N + 3n = 9 + 3 Combine like terms: -3 + 3 = 0 0 + N + 3n = 9 + 3 N + 3n = 9 + 3 Combine like terms: 9 + 3 = 12 N + 3n = 12 Add '-3n' to each side of the equation. N + 3n + -3n = 12 + -3n Combine like terms: 3n + -3n = 0 N + 0 = 12 + -3n N = 12 + -3n Simplifying N = 12 + -3n
| 10x+2=132 | | q^2+9q+7=0 | | g^2+3g-4=0 | | 8n=192 | | 2sin^2X=1-4cosx | | 4x^2+25x-15=0 | | 6x^3+3x^2+10x+5=0 | | 1-4cosx=0 | | A+90-15=120 | | 0.9x=-12000 | | 4x=9k^2 | | 2x^2+4x=x^2-2x | | 6r+2-3r+r-10=20 | | 9x^2-25=18x^2-50 | | 4y+17=-7x | | 0.9x+12000=0 | | 40x^2-30x-135=0 | | 68=-4-4(4m-2) | | 6v/v-10 | | H(h^2-3)-2h=h(h-2)-12 | | 2.75x+35=2.30x+95 | | 63=3(-4-5r) | | 36/7=144/x | | 4cos^20+6cosx+2=0 | | 14=2/3p=8 | | 83=-3x-5(2x-1) | | r(r-6)=7 | | 150=-6(4x-5) | | 4cos^2x-6cosx+2=0 | | (3-2i)+(-5+3i)=0 | | 289u^2-1=0 | | t^2-2t=3t+24 |